Kolaborasi Tausiyah dan Tahsin sebagai Strategi Penguatan Keislaman dalam Pengajian Ibu-Ibu - Delfia Herwanis; Suminah Suminah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service article seeks to enhance the religious literacy and Qur'anic recitation skills (tahsin) of women aged 45 and above in the Aceh Tengah region. The program consists of 90-minute weekly meetings, incorporating 45 minutes of Islamic motivating lectures (tausiyah) and 45 minutes of guided tahsin. This effort employs participatory and reflective methodologies to address the spiritual and technological dimensions of faith practices. Results demonstrate that participants exhibited notable enhancement in their confidence in reading the Qur'an and conveyed a heightened emotional and spiritual connection to Islamic ideals. This program emphasised the significance of accessible, consistent, and compassionate Islamic education for adult learners. The results indicate additional chances for replication in analogous sociocultural environments.